Pola Penanaman Nilai-Nilai Kemanusiaan di Perguruan Silat Ki Ageng Pandan Alas Ranting Kademangan Blitar - Reana Oktiana Putri; Miranu Triantoro; Minto Santoso; Arik Cahyani (Jurnal Pendidikan dan Kewarganegara Indonesia, 2025)
This study aims to describe the pattern of instilling human values at Ki Ageng Pandan Alas Martial Arts School, Kademangan Branch, Blitar. The research employed a descriptive qualitative approach with a phenomenological design. Data were collected through participatory observation, in-depth interviews using snowball sampling, and documentation, then analyzed using Miles & Huberman’s interactive model. The findings reveal that value transmission is carried out gradually through regular training, the trilogy of spirituality (hablum minallah, hablum minannas, rahmatan lil alamin), and the school’s greeting symbolized by the keris sigar penjalin. Methods applied include lectures, exemplary behavior, habituation, games, reward and punishment, value discussions, internalization, and real-life activities. The media consist of physical elements (uniforms, belts, symbols, and training equipment) and non-physical ones (teachings, role models, traditions). The study confirms that martial arts schools can serve as a medium for character education, particularly in fostering religiosity, empathy, respect, self-control, and social care. These findings enrich the discourse on value education and provide references for educational institutions, families, and communities.